A Theory of Vertical Fiscal Imbalance - Robin Boadway; Jean-Francois Tremblay (Queen's University, Department of Economics, 2006)
This paper examines how sequential decision-making by two levels of government can result in vertical fiscal imbalances (VFI). Federal-regional transfers serve to equalize the marginal cost of public funds between regions hit by different shocks. The optimal vertical fiscal gap minimizes the efficiency cost of taxation in the federation as a whole. The analysis shows how the existence of vertical fiscal externalities, leading regional governments to overprovide public goods, can induce the federal government to create a VFI by selecting transfers that differ from the optimal fiscal gap. When the federal government can commit to its policies before regional governments select their level of expenditures, the VFI will generally be negative. In the absence of commitment, the equilibrium transfer is unambiguously larger than the optimal fiscal gap, resulting in a positive VFI. In an intertemporal setting, the VFI has implications for the sharing of debt between the federal and regional governments.
Keywords: H72; H73; H77; 330; vertical fiscal imbalance; federal-regional transfers; commitment; fiscal externalities